Proceedings of the 1993 ACM/IEEE Conference on Supercomputing - Supercomputing '93 1993
DOI: 10.1145/169627.169651
|View full text |Cite
|
Sign up to set email alerts
|

A parallel adaptive fast multipole method

Abstract: We present parallel versions of a representative N-body application that uses Greengard and Rokhlin's adaptive Fast Multipole Method (FMMJ While parallel implementations of the umform FMM are straightforward and have been developed on alfferent architectures, the aalzptive version complicates the task of obtaining eflective parallel peflormance owing to the nonunz~onn and dynamically changing nature of the problem &mains to which it is applied.We propose and evaluate two techniques for providing load balancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 11 publications
0
64
0
Order By: Relevance
“…The idea to parallelize the FMM is not new and there are publications that address some basic issues [9,19,20,21,24]. However these publications are mostly related to the development of more coarse-grained parallel algorithms.…”
mentioning
confidence: 99%
“…The idea to parallelize the FMM is not new and there are publications that address some basic issues [9,19,20,21,24]. However these publications are mostly related to the development of more coarse-grained parallel algorithms.…”
mentioning
confidence: 99%
“…To our knowledge, the only parallel implementation of this type of method prior to ours is a shared-memory implementation of a 2-D version of the Greengard-Rokhlin method [25]. In previous work [13,14], we have shown that efficient scalable code can be produced in data parallel languages for nonadaptive versions of Anderson's method.…”
Section: Hierarchical N-body Methodsmentioning
confidence: 98%
“…On modern multicore and GPU architectures, this requires parallelization of the algorithm. The FMM has been sought to be parallelized almost since its invention -see e.g., [5,6,7,8]. However, these works are mostly related to more coarse-grained parallel algorithms and often focus on tree codes rather than the FMM.…”
Section: Fast Multipole Methods and Scalabilitymentioning
confidence: 99%